Genomic evidence of positive selection highlights functional divergence associated with environmental resilience in central and West African indigenous cattle - Bitew, M.K.; Paguem, A.; Abanda, B.; Achukwi, D.M.; Manchang, K.T.; Preuß, S.; Hanotte, Olivier H.; Senczuk, G.; Renz, A.; Eisenbarth, A.; Pilla, F. (Nature Research, 2026)
African indigenous cattle harbor rich genetic diversity shaped by long-term adaptation to tropical climates and endemic diseases, notably trypanosomiasis. To investigate the genetic basis of natural disease resistance, we analyzed 33,147 SNPs in 1,047 individuals from 17 breeds using complementary selection scans (iHS, XP-EHH, and Rsb) in a multi-cohort framework. Fifteen pairwise comparisons across six breed groups enabled robust detection of recent positive selection, capturing both within-breed and breed-specific adaptive signals. We identified 229 selective regions, with 47 outlier SNPs consistently detected by multiple methods. Selection signals were enriched on chromosomes 5, 7, and 29, containing candidate genes such as ATF4, PKNOX2, DNAJB7, TEF, NFE2, and several SPINK and HOXC family members, many associated with immune function and trypanosome challenge response. These genomic regions represent promising targets for the development of breeding strategies aimed at enhancing disease resilience. By identifying genomic regions under selection, this study provides interesting insights for sustainable livestock improvement and conservation efforts in West and Central Africa. Our findings support the integration of indigenous genetic resources into breeding programs designed to optimize productivity while maintaining resilience to environmental and disease pressures.